2019
DOI: 10.1177/1756284819842748
|View full text |Cite
|
Sign up to set email alerts
|

Switching from infliximab to biosimilar in inflammatory bowel disease: overview of the literature and perspective

Abstract: Background: Biological therapy has revolutionized the treatment of inflammatory bowel disease (IBD). After the expiration of patents for biological innovator products, development of biosimilars increased. CT-P13 was the first biosimilar approved for the same indications as the reference product; however, the approval was based on extrapolated data from rheumatoid arthritis and ankylosing spondylitis. Our aim was to review clinical studies about switching from originator infliximab (IFX-O) to bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 80 publications
1
14
0
2
Order By: Relevance
“…For extrapolation to be permitted, biosimilarity must have been demonstrated in in vitro, nonclinical, and clinical studies, and the rationale for extrapolation must be scientifically justifiable [3]. Today, approval of CT-P13 in IBD is also supported by real-world evidence and clinical trial data [34,[120][121][122][123], including from the randomized, double-blind, noninferiority phase IV NOR-SWITCH study [120] and a Hungarian prospective observational cohort study [124]. To our knowledge, no published clinical trials evaluating the approved adalimumab biosimilars ABP 501, BI 695501, or SB5 in IBD, or real-world evidence for other infliximab biosimilars exist.…”
Section: Gastroenterologists' Perspective: Earlier Introduction Of Bimentioning
confidence: 99%
“…For extrapolation to be permitted, biosimilarity must have been demonstrated in in vitro, nonclinical, and clinical studies, and the rationale for extrapolation must be scientifically justifiable [3]. Today, approval of CT-P13 in IBD is also supported by real-world evidence and clinical trial data [34,[120][121][122][123], including from the randomized, double-blind, noninferiority phase IV NOR-SWITCH study [120] and a Hungarian prospective observational cohort study [124]. To our knowledge, no published clinical trials evaluating the approved adalimumab biosimilars ABP 501, BI 695501, or SB5 in IBD, or real-world evidence for other infliximab biosimilars exist.…”
Section: Gastroenterologists' Perspective: Earlier Introduction Of Bimentioning
confidence: 99%
“…Incorrect or misleading conclusions about biosimilars have been published in scientific literature, enabling others to quote the misleading conclusions as fact and creating a false narrative. An article on the ethics of biosimilars [ 33 ] cited three literature reviews [ 34 36 ] to conclude that the safety and efficacy of switching once from a reference product to a biosimilar is still controversial, and therefore physicians are ethically obligated to inform prospective biosimilar recipients of this “fact.” However, a close examination of the three reviews found that none of them identified any specific safety or lack of efficacy concern related to switching once from a reference biologic to a biosimilar. Another recent review of 178 switching studies also concluded that for the products studied, a single switch is not intrinsically linked to an increase in immunogenicity, safety, or efficacy issues [ 37 ].…”
Section: Types Of Biosimilar Disparagement and Misinformationmentioning
confidence: 99%
“…There is some concern that switching a patient currently in remission on a biologic to a biosimilar could potentially have uncertain or adverse results ( 11 , 32 ), especially in cases of comorbidity or other complex patient or disease-specific characteristics ( 33 ). Two 2018 meta-analyses of research into clinical outcomes of switching to biosimilars came to different conclusions regarding safety: one concluded that “there are important evidence gaps around the safety of switching” ( 34 ), while the other claimed their results provided reassurance that “the risk of immunogenicity-related safety concerns or diminished efficacy is unchanged after switching from a reference biologic to a biosimilar medicine.” ( 35 ) And another review of 29 studies concerning switching for patients with inflammatory bowel disease concluded that “scientific and clinical evidence is lacking regarding reverse switching, multiple switching and cross-switching among biosimilars” ( 36 ). Given such inconsistencies, and since many patients in remission on a reference biologic are likely to have experienced multiple failed treatments in the past, some patients may want to remain on the same drug ( 37 ).…”
Section: Biologics and Biosimilarsmentioning
confidence: 99%